Effects of salinity on proline and lipid peroxidation content on lowland tomato grown under soilless culture system - Ahmad, Nur Fatin; Megat Wahab, Puteri Edaroyati; Hassan, Siti Aishah; Sakimin, Siti Zaharah (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
A research has been carried out in order to determine effects of salinity in lowland tomato cultivar Pearl. Seeds of cultivar Pearl were sown in 100% of peat for two weeks before transplanted into polybags containing 100% of coconut coir dust. A fertigation system was installed in the glasshouse and 15-days old seedlings were irrigated via drip irrigation with basic nutrient solution using Cooper formulation. Six days later, salt treatments were initiated by adding NaCl to nutrient solution using 0, 70 and 140 mM and continued for six weeks. The treatments were assigned in Completely Randomized Design (CRD). Differences in growth, relative water content, proline accumulation and lipid peroxidation of Pearl was identified to put forward for sensitivity of the cultivar. Shoot and root dry weight of Pearl was markedly inhibited with the increasing concentrations of NaCl. Relative water content was slightly affected by increasing level of NaCl. Proline content in the leaves was significantly increased with more than 50% increment as NaCl level increased, and showed the highest at 2.5 mM NaCl. No significant effect of NaCl treatment was recorded for lipid peroxidation, but both 2.5 and 10 mM NaCl showed almost the same content. This study suggested that lowland tomato cultivar Pearl was moderately sensitive to salinity by inducing high proline and inhibited growth as well as relative water content which can be a reliable indicator for salinity stress especially plants grown under soilless culture system.